The Orang Asli: First on the Land, Last in the Plan - Colin Nicholas (Kajian Malaysia, 2003)
The Orang Asli (Original Peoples) are the indigenous minority peoples of Peninsular Malaysia. They are the descendants of the early inhabitants of the peninsula before the establishment of the Malay kingdoms. They number 133,775 today, representing a mere 0.5%o of the national population. Anthropologists and administrators have traditionally regarded the Orang Asli as consisting of three main groups which in themselves comprise several distinct tribes or subgroups. The main groups are the Negrito (Semang), the Senoi, and the Aboriginal-Malay. Each tribal group is further divided into various subgroups as given overleaf.